Modern restful api dls and frameworks for restful web services api schema modeling, documenting, visualizing - Malakhov, K.S.; Kurgaev, A.P.; Velychko, V.Yu. (Інститут програмних систем НАН України, 2019)
The given paper presents an overview of modern RESTful API description languages (belongs to interface description languages set) – OpenAPI, RAML, WADL, Slate – designed to provide a structured description of a RESTful web APIs (that is useful both to a human and for automated machine processing), with related RESTful web API modelling frameworks. We propose an example of the schema model of web API of the service for pre-trained distributional semantic models (word embeddings) processing. This service is a part of the “Personal Research Information System” services ecosystem – the “Research and Development Workstation Environment” class system for supporting research in the field of ontology engineering: the automated building of applied ontology in an arbitrary domain area as a main feature; scientific and technical creativity: the automated preparation of application documents for patenting inventions in Ukraine. It also presents a quick look at the relationship of Service-Oriented Architecture and Web services as well as REST fundamentals and RESTful web services; RESTful API creation process.Problems in programming 2018; 4: 59-68